(untitled) (Interdisciplinary Studies Journal, 2025)
This article addresses the role of the History of Law in the training of law professors in Brazil, reflecting on how the articulation between tradition and innovation can promote a more critical and democratic legal education in the country. It is a theoretical study, with a methodology based on literature review and documentary analysis. The study starts from the understanding that Brazilian legal education has historically reproduced technicist and exclusionary models, disconnected from social demands and the potential of digital technologies. The History of Law is approached as a formative tool capable of broadening the understanding of the historical foundations of legal institutions and fostering a more reflective teaching practice, especially through the use of technologies as a resource to enhance training and democratize access to legal knowledge. The results indicate that integrating a historical perspective into the training process, combined with the critical use of technologies, can transform legal education toward more dialogical, emancipatory, and socially committed practices.